Implementation of Academic Supervision in Improving the Quality of Learning at SMA N 2 Batang, Batang Regency - Widyawati, Dinar (Universitas Syiah Kuala, 2024)
This study aims to describe and analyze the implementation of academic supervision in improving the quality of learning at SMA N 2 Batang in 2024. This study uses a qualitative approach with data collection techniques in the form of observation, interviews and document searches. The data obtained were analyzed using data reduction, data presentation and verification through several informants, namely the principal, vice principal of curriculum, vice principal of student affairs, supervisor team, teachers and students. The results of the study revealed that the implementation of academic supervision in improving the quality of learning at SMA N 2 Batang was carried out through three stages, namely the first stage is planning which consists of activities to identify and plan objectives, design learning strategies and design assessment processes. The second stage is the implementation of academic supervision consisting of pre-observation, observation and post-observation. The third stage is follow-up activities consisting of coaching and in-house training activities. The results of the study revealed three findings, namely: 1) The planning of the academic supervision program at SMA N 2 Batang is centered on the principal so that the program runs well and is able to improve the quality of learning, 2) The implementation of academic supervision at SMA N 2 Batang is carried out through an indirect approach with a humanistic pattern so that good coordination is established between teachers and supervisors, 3) Follow-up to academic supervision at SMA N 2 Batang consists of coaching and providing training to improve teacher competence in order to support improving the quality of learning. Based on the results of the study and discussion, it can be concluded that the implementation of academic supervision at SMA N 2 Batang has been carried out well because it is carried out according to procedures so that it is able to improve the quality of learning which is seen from the increase in teacher competence starting from planning, implementing, and evaluating learning so that it can stimulate students to focus and be active in learning.